Field Guide to Sharks, Rays & Chimaeras of Europe and the Mediterranean - Ebert, David A.; Dando, Marc (Wild Nature Press, 2020)
The definitive field guide to all the sharks, rays and chimaeras of the European Atlantic and MediterraneanThe waters of the northeast Atlantic and Mediterranean Sea are home to an amazing variety of sharks, rays and chimaeras. This comprehensive and easy-to-use field guide covers all 145 species found in the Mediterranean, the waters of the European Atlantic and Iceland, along all the Scandinavian coasts, in the Black Sea and as far south as the Canary Islands. Detailed species accounts describe key identification features, habitat, biology and status. Every species account comes with a colour distribution map, a depth guide, at-a-glance icons and colour illustrations. This must-have field guide also features illustrated key guides that enable you to accurately identify down to species, comparison plates of similar species, illustrations of eggcases where known and plates of teeth.The first field guide to cover all 145 speciesFeatures hundreds of colour illustrations, photos, maps and diagramsDescribes key features, habitat, biology and statusIncludes depth guides, at-a-glance icons, key guides and teeth plates